PENGARUH KEADAAN EKONOMI ORANGTUA, DISIPLIN MELALUI PERHATIAN ORANGTUA TERHADAP HASIL BELAJAR - Nurhayati Nurhayati; I Komang Winatha; Nurdin Nurdin (FKIP Unila, 2014)
This research is aimed at finding the influence of parent’s economic condition and dicipline through parent’s afection towards result on IPS Terpadu learning.The method used verificative descriptive method.The result of the study showed, (1)there is an influence of parent’s economic condition towards parent’s affection, (2)there is an influence of learning dicipline towards parent’s affection, (3)there is an influence of parent’s economic condition towards result on IPS Terpadu learning, (4)there is an influence of learning dicipline towards result on IPS Terpadu learning, (5)there is an influence of parent’s affection towards result on IPS Terpadu learning, (6)there is an influence of parent’s economic condition towards result on IPS Terpadu learning through parent’s affection, (7)there is an influence of learning dicipline towards result on IPS Terpadu learning through parent’s affection, (8)there is an influence of parent’s economic condition and learning dicipline towards parent’s affection, (9)there is an influence of parent’s economic condition and learning dicipline through parent’s affection towards result on IPS Terpadu learning. Penelitian bertujuan untuk mengetahui pengaruh keadaan ekonomi orangtua dan disiplin melalui perhatian orangtua terhadap hasil belajar IPS Terpadu.Metode yang digunakan adalah metode deskriptif verifikatif.Hasil analisis menunjukkan, (1)ada pengaruh keadaan ekonomi orangtua terhadap perhatian orangtua, (2)ada pengaruh disiplin belajar terhadap perhatian orangtua, (3)ada pengaruh keadaan ekonomi orangtua terhadap hasil belajar IPS Terpadu, (4)ada pengaruh disiplin belajar terhadap hasil belajar IPS Terpadu, (5)ada pengaruh perhatian orangtua terhadap hasil belajar IPS Terpadu, (6)ada pengaruh keadaan ekonomi orangtua terhadap hasil belajar IPS Terpadu melalui perhatian orangtua, (7)ada pengaruh disiplin belajar terhadap hasil belajar IPS Terpadu melalui perhatian orangtua, (8)ada pengaruh keadaan ekonomi orangtua dan disiplin belajar terhadap perhatian orangtua, (9)ada pengaruh keadaan ekonomi orangtua dan disiplin belajar melalui perhatian orangtua terhadap hasil belajar IPS Terpadu. Kata kunci: disiplin, keadaan ekonomi, perhatian orangtua